2019
DOI: 10.1136/annrheumdis-2019-215743
|View full text |Cite
|
Sign up to set email alerts
|

Metagenome-wide association study of gut microbiome revealed novel aetiology of rheumatoid arthritis in the Japanese population

Abstract: ObjectiveThe causality and pathogenic mechanism of microbiome composition remain elusive in many diseases, including autoimmune diseases such as rheumatoid arthritis (RA). This study aimed to elucidate gut microbiome’s role in RA pathology by a comprehensive metagenome-wide association study (MWAS).MethodsWe conducted MWAS of the RA gut microbiome in the Japanese population (n case=82, n control=42) by using whole-genome shotgun sequencing of high depth (average 13 Gb per sample). Our MWAS consisted of three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
120
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(137 citation statements)
references
References 44 publications
4
120
0
Order By: Relevance
“…One SNP (rs1230666) was found to be independently associated with RA development and therefore removed, following its removal the remaining 25 SNP’s failed to demonstrate the microbiome as a casual factor for RA development ( Inamo, 2019 ), suggesting the observed microbial dysbiosis in RA is a secondary phenomenon. However, Alpizar-Rodriguez et al (2019a) has highlighted that microbial dysbiosis does not always equate to decreases in microbial taxa, and rather is it a compositional shift of the microbiome that is driving the RA dysbiosis ( Kishikawa et al, 2020 ). Therefore MR analysis based a selection of SNP’s that are known to affect the gut microbiome by decreasing the numbers of taxa present within the gut is unlikely to yield a casual effect, given an arbitrary decrease of taxa is in contradiction to the current observational studies.…”
Section: Causality and The Microbiomementioning
confidence: 99%
“…One SNP (rs1230666) was found to be independently associated with RA development and therefore removed, following its removal the remaining 25 SNP’s failed to demonstrate the microbiome as a casual factor for RA development ( Inamo, 2019 ), suggesting the observed microbial dysbiosis in RA is a secondary phenomenon. However, Alpizar-Rodriguez et al (2019a) has highlighted that microbial dysbiosis does not always equate to decreases in microbial taxa, and rather is it a compositional shift of the microbiome that is driving the RA dysbiosis ( Kishikawa et al, 2020 ). Therefore MR analysis based a selection of SNP’s that are known to affect the gut microbiome by decreasing the numbers of taxa present within the gut is unlikely to yield a casual effect, given an arbitrary decrease of taxa is in contradiction to the current observational studies.…”
Section: Causality and The Microbiomementioning
confidence: 99%
“…Moreover, by comparing the results of a RA microbial GWAS with those of a RA GWAS, the authors determined a population-specific biological pathway linking the metagenome and host genome. These results newly revealed a relationship between the gut microbiome, host genome and RA pathology, and thus represent a new reference that better clarifies the aetiology of RA 6. Certainly, this study is expected to explain the sexual dimorphism of RA because of the nine strains mentioned by Kishikawa et al , Gardnerella , or G. vaginalis , is a clinical indicator of vaginitis in female patients.…”
mentioning
confidence: 53%
“…In this study, faecal samples were subjected to whole-genome shotgun sequencing. Through case–control phylogenetic association tests conducted using a generalised linear regression model, nine strains present at significantly higher levels of abundance in patients with RA were finally identified, namely Prevotella denticola , Gardnerella , Gardnerella vaginalis , Porphyromonas somerae , Prevotella marshii , Prevotella disiens , Bacteroides sartorii , Prevotella corporis and Prevotella amnii 6. Moreover, the authors clearly demonstrated correlations of multiple Prevotella spp beyond P. copri with the aetiology of RA.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…However, recent data strongly suggest only a minor influence of genetics on microbiota composition 6. Furthermore, no studies have ever found significant differences in alpha or beta diversities between RA cases and controls, despite significant differences in specific bacterial taxa (ie, Prevotella copri ) 2 7. Thus, the exposure analysed by the author does not represent a relevant measure of dysbiosis in RA.…”
mentioning
confidence: 86%